First implementation and results of online adaptive radiotherapy for cervical cancer based on CT-Linac combination - Jiang, Dazhen; Yang, Chunxu; Sun, Shaoxing; Wang, Dajiang; Xiao, Zhizhi; Hu, Jie; Mei, Zijie; Xie, Conghua; Liu, Hui; Qiu, Hui; Wang, Xiaoyong (Frontiers in Oncology, 2024)
PurposeTo assess the dosimetric effectiveness of image-guided radiation treatment (IGRT) and online adaptive radiation therapy (oART) for cervical cancer. As well as survival follow-up was conducted to validated the safety and efficacy of oART.MethodsA total of 15 cervical cancer patients were enrolled. oART was performed on a CT-integrated linear accelerator. The initial plan was revised to include the distribution of IGRT dose using daily fan-beam CT (FBCT) images, after which the distinctions between ART and IGRT in terms of target coverage and organs at risk (OARs) sparing were analyzed. Survival follow-up was conducted to validated the safety and efficacy of oART in this group.ResultsPTV Dmax value decreased by 1.23 Gy in the ART plan when compared to that in the IGRT plan; PTV D95 increased by 1.34 Gy; PTV V50 coverage increased by 4.86%; CTV coverage increased by 3.02%; PTV D2cc of the colon, rectum, and small intestine decreased by 1.24 Gy, 1.29 Gy, and 1.12 Gy, respectively. The V10 and V30 of the pelvis increased by 1.27% and 0.56%, respectively, while the V30 of the left and right femoral heads dropped by 2.82% and 3.41%, respectively. Except for the pelvic changes, all other differences were statistically significant (p < 0.01). The average time for the ART procedure was 21.22 min (range: 18.72–24.90 min). The median follow-up time is 28.0 months. Median event-free survival and overall survival were not reached. EFS rate and OS rate at 3 years were 79.4% and 92.9%.ConclusionOnline ART for cervical cancer can minimize the dose of OARs and enhance the target volume coverage significantly when compared to IGRT with satisfied survival time.